FORMATION STUDENTS’ ICT COMPETENCE: CASE STUDY - Morze, Nataliia; Barna, Olha; Kuzminska, Olena; Vember, Viktoriia (Електронне наукове фахове видання “ВІДКРИТЕ ОСВІТНЄ Е-СЕРЕДОВИЩЕ СУЧАСНОГО УНІВЕРСИТЕТУ”, 2017)
This article shows theoretical foundations and experience of research on the formation students’ ICT competence, which was conducted based on the TOTE model. Described criteria of information and communication competence, proposed the model for the formation of ICT competence of high school students during the process of computer science education and to verify its effectiveness by conducting a monitoring study. The results of the experiment determined the impact of way of formation, method of formation and form of assisstance on the formation of students’ ICT competence. DOI: https://doi.org/10.28925/2414-0325.2017.3.89s9